Effects of nitrogen enrichment on tree carbon allocation: A global synthesis. Issue 3 (6th December 2019) - Li, Weibin; Zhang, Hongxia; Huang, Guozhu; Liu, Ruixue; Wu, Hongjing; Zhao, Chuanyan; McDowell, Nate G.
Abstract: Aim: Increased atmospheric nitrogen deposition may have profound effects on tree carbon allocation dynamics. However, a comprehensive understanding of how nitrogen (N) enrichment influences carbon (C) allocation across plant functional processes and tree organs in individual trees remains elusive. Location: Global forest ecosystems. Time period: 1990–2018. Major taxa studied: Trees. Methods: We compiled data from 75 N addition experiments and conducted a meta‐analysis to evaluate the responses of C source (photosynthesis), sinks (growth and respiration) and storage (non‐structural carbohydrate concentrations) in different tree organs (foliage, above‐ground wood and roots) to N enrichment. Results: N enrichment significantly enhanced C supply via photosynthesis (+39.6%, n = 128). C allocation to growth (biomass increment/production) significantly increased in foliage (+15.9%, n = 68) and above‐ground wood (+31.8%, n = 64; bole, branch, stem and/or twig) with increasing N availability, but not in roots, whereas allocation increased in roots via increasing fine root turnover rate (+22.6%, n = 11). N fertilization significantly increased C allocation to respiration in above‐ground wood (+46.6%, n = 12) and roots (+5.5%, n = 57), but not in foliage. N addition decreased non‐structural carbohydrate (NSC) concentrations in foliage (−5.4%, n = 16) and roots (−5.0%, n = 21), but increased NSC in above‐ground wood (+6.1%, n = 22). In addition, N enrichment effects were strongly affected by moderator variables. Main conclusions: Our results demonstrate that N addition increased C allocation to growth and respiration more strongly than C allocation to NSC storage, and increased C allocation to above‐ground parts more strongly than to below‐ground parts. Our results are useful for better understanding the response of tree functional processes at organ level to N enrichment. The existing data also reveal that more long‐term experimental studies on mature trees in tropical and boreal forests are urgently needed to provide a basis for forecasting tree responses to N enrichment at the global scale.